EASINESS: E. coli Assisted Speedy affINity-maturation Evolution SyStem - Zhang, Hai-nan; Xue, Jun-biao; Wang, Aru Ze-ling; Jiang, He-wei; Merugu, Siva Bhararth; Li, Da-wei; Tao, Sheng-ce (Frontiers in Immunology, 2021)
Antibodies are one of the most important groups of biomolecules for both clinical and basic research, and have been developed as potential therapeutics. Affinity is the key feature for biological activity and clinical efficacy of an antibody, especially of therapeutic antibodies, and thus antibody affinity improvement is indispensable and still remains challenging. To address this issue, we developed the E. coli Assisted Speed affINity-maturation Evolution SyStem (EASINESS) for continuous directed evolution of Ag-Ab interactions. Two key components of EASINESS include a mutation system modified from error-prone DNA polymerase I (Pol I) that selectively mutates ColE1 plasmids in E. coli and a protein-protein interaction selection system from mDHFR split fragments. We designed a GCN4 variant which barely forming homodimer, and during a single round of evolution, reversed the homodimer formation activity from the GCN4 variant to verify the feasibility of EASINESS. We then selected a potential therapeutic antibody 18A4Hu and improved the affinity of the antibody (18A4Hu) to its target (ARG2) 12-fold in 7 days while requiring very limited hands-on time. Remarkably, these variants of 18A4Hu revealed a significant improved ability to inhibit melanoma pulmonary metastasis in a mouse model. These results indicate EASINESS could be as an attractive choice for antibody affinity maturation.